Aboveground Deadwood Biomass and Composition Along Elevation and Land-Use Gradients at Mount Kilimanjaro - Komposch, Armin; Ensslin, Andreas; Fischer, Markus; Hemp, Andreas (Frontiers in Ecology and Evolution, 2022)
Deadwood is an important structural and functional component of forest ecosystems and their biodiversity. It is known that deadwood can make up large portions of the total aboveground biomass and therefore plays an important role in the terrestrial carbon (C) cycle. Nevertheless, quantitative studies on this topic are scarce, especially for the tropics. In this study, we conducted a deadwood inventory along two environmental gradients at Mt. Kilimanjaro, Tanzania. On the one hand, we used a huge elevation gradient (3690 m) along the southern slope of the mountain to investigate how deadwood is accumulated across different climate and vegetation zones. On the other hand, we compared habitats with different land-use intensities and disturbance histories with natural forests, to assess the anthropogenic influence on deadwood accumulation. In our inventory, we distinguished coarse woody debris (CWD) and fine woody debris (FWD). Furthermore, we looked at the C and nitrogen (N) content of deadwood and how the ratio of these two elements changed along decomposition stages and elevation. Total amount of deadwood ranged from 0.07 ± 0.04 to 73.78 ± 36.26 Mg ha-1 (Mean ± 1 SE). Across the elevation gradient, total deadwood was highest at mid-elevations and reached a minimum close to 0 in very low, as well as high altitudes. These unimodal patterns were mainly driven by the corresponding amount of live aboveground biomass and the combined effects of climate and decomposer communities. Land conversion from natural forests into traditional homegardens and commercial plantations, as well as frequent burning significantly reduced deadwood biomass, but not past selective logging after 30 years of recovery time. Furthermore, we found an increase in deadwood C content with increasing altitude. Our study shows that environmental gradients, especially temperature and precipitation, as well as different anthropogenic disturbances can have considerable effects on both, the quantity and composition of deadwood in tropical forests.